Odpowiedzi

Najlepsza Odpowiedź!
2010-01-26T16:23:08+01:00
a)
2(x-1)+(y+2)=4
3(x+1)-(y-3)=7

2x-2+y+2=4
3x+3-y+3=7 |-6

2x+y=4
3x-y=1

5x=5 |/5
x=1
2x+y=4
2+y=4 |-2
y=2

ODP: x=1 y=2

b)
3(x+2)+2(y-2)=1
(x+2-4)-y-1=1

3x+6+2y-4=1
x+2-4-y-1=1

3x+2y+2=1 |-2
x-y-3=1 |+3

3x+2y=-1
x-y=4 |*2

3x+2y=-1
2x-2y=8

5x=7 |/5
x=⁷/₅

x-y=4
⁷/₅-y=4 |+y -4
⁷/₅-4=y
-¹³/₅=y

ODP: x=⁷/₅ y=-¹³/₅

c)
-2(x-3)-(4-y)=0
5(x+1)+3(2-y)=17

-2x+6-4+y=0
5x+5+6-3y=17

-2x+2+y=0
5x+11-3y=17

y-2x=-2 |*3
5x-3y=6

3y-6x=-6
5x-3y=6

-x=0
x=0

3y-6x=-6
3y-0=-6 |/3
y=-2

ODP: x=0 y=-2

d)
4(x+3)-2(x+1)=0
2(y-1)-(3-y)=-10

4x+12-2x-2=0
2y-2-3+y=-10

2x+10=0 |-10
3y-5=-10 |+5

2x=-10 |/2
3y=-5 |/3

x=-5
y=-⁵/₃

ODP: x=-5 y=-⁵/₃